Can heritage bring peace and prosperity? - Babić, Darko (2006)
What is heritage? Where does it exist? What is knowledge versus wisdom, and why is it important? The foundation of heritage lies within ‘ elements of heritage’ , those pretty big amounts of tangible (objects, monuments, sites...) as well as intangible (customs, languages, music...) ingredients which are still predominately defined as ‘ heritage’ . The theoretical approach is examined with three case studies from Croatia.